Proses Pengeringan Daun Tarum (Indigofera zollingeriana) Menggunakan Alat Pengering Hybrid - Lani, Lisa May; Suharyatun, Siti; Kuncoro, Sapto; Warji, Warji (abe.fp.unila.ac.id, 2024)
. Tarum (Indigofera zollingerina) is a land plant belonging to the Leguminosa family. This plant grows widely in Sumatra and Java. Tarum leaf flour contains crude protein, crude fat or ether extract and crude fiber. Tarum leaf flour contains mineral content, namely Ca, P, Mg and complete amino acids and is almost the same as soybean meal. The population of beef cattle and goats in Indonesia is currently continuing to increase, it is recorded that the population of beef cattle in Indonesia in 2022 will be around 18,061,000 heads and 19,397,960 goats spread throughout Indonesia. Where is the data on the population of beef cattle and goats increased compared to the previous year (2021) which was only 18,053,710 head of cattle and 19,229,067 head of goats. The use of hybrid dryers is an effective choice for drying Tarum leaves. Testing materials using electricity and solar energy (hybrid) was carried out for 8 hours. Testing materials using an oven was carried out for 6 hours. Tests using direct solar energy (traditional) were carried out drying for 12 hours. Proximate analysis is one way that has often been used to determine the value of nutrient content in raw materials or food. From the results of testing the proximate content of Tarum leaf flour using a hybrid dryer obtained; moisture content 10.52%, protein 22.47%, fat 11.69%, fiber 8.75%, ash content 10.70% and BETN 35.87%. Drying using oven obtained; moisture content 10.98%, protein 17.54%, fat 12.87% fiber 6.78%, ash content 9.72% and BETN 42.11%. Drying using direct solar energy (traditional) obtained; moisture content 12.31%, protein 18.54%, fat 8.64%, fiber 8.54%, ash content 14.27% and BETN 37.7%. Keywords: Drying, Hybrid, Proximate Test, Tarum.